United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
The Selected Issues paper examines the dynamics of the inflation process in the United Kingdom, particularly the influence of external shocks. The paper provides a brief summary of existing empirical work. It presents the expectations-augmented Phillips curve model used in the analysis. The basic conclusion is that low inflation in recent years can be explained reasonably well by a combination of increased competitive pressures. The paper also presents some estimates of the degree of possible overvaluation in housing prices and outlines the links between housing prices and the macroeconomy.